Diagnosis of the avocado crop in the municipality of General Heliodoro Castillo - Otero-Sánchez, Marco Antonio; Velasco-Velasco, Lidia; Díaz-Núñez, José Luis; Vélez-Torres, Marcelina; Flores-Hernández, Luis Antonio (Revista Mexicana de Ciencias Agrícolas, 2026)
In recent years, the avocado crop has aroused great interest among farmers in the state of Guerrero, thanks to its economic importance, profitability and nutritional and nutraceutical benefits. In addition, it is a high-demand product both at home and abroad. However, various factors limit the scope of the crop’s potential yield, such as edaphic conditions, nutritional status, climate, pest and disease incidence and water resources, among others. This research aimed to carry out an edaphic characterization, nutritional diagnosis of the vegetative tissue and evaluation of the incidence of pests in the avocado crop in the locality of Izotepec, municipality of General Heliodoro Castillo, in the region Sierra of Guerrero. To this end, soil and leaf tissue sampling was carried out in an orchard in the study area in order to determine the physical and chemical composition of the soil and leaf tissue, as well as the incidence of pests and diseases. The results indicated that the soil texture is suitable for the avocado crop. Nevertheless, deficiencies in nutrient content, soil pH below optimal values, and low concentration of essential elements, such as N, P, K, Mg, S, Mn and B, in leaf tissue were identified. In addition, the susceptibility of pests and nutritional deficiencies was confirmed, which can be prevented and controlled through an integrated management of plant nutrition and health.
Keywords: nutrient composition; organic matter; pH; texture